IMPACT OF THE AUSTRALIAN GOVERNMENT ECONOMIC STIMULUS PACKAGE ON PROCUREMENT - Putnam, Emily (The journal of contemporary issues in business and government, 2010)
In February 2009, the Federal Government announced a42 billion ‘Nation Building – Economic Stimulus Plan’ (the Plan) in response to the Global Financial Crisis. The Plan involved a massive spending program on building infrastructure for the key areas of education, community infrastructure, road and rail, housing and renewable energy. This paper will examine two key areas of the Plan– education and renewable energy – with a focus on their impact on procurement and the lessons to be learnt. The education infrastructure spending program titled ‘Building the Education Revolution’ and the original renewable energy program which involved the Home Roofing Insulation Scheme have both received a plethora of media attention and public feedback, a large proportion of which has been negative. While generally the Plan has been considered beneficial for the Australian economy and a contributing factor to the country’s resilience to the worst of the Global Financial Crisis as seen in many other countries, the delivery of these key areas of the Plan have received criticism for the varying outcomes and benefits delivered for the procurement spend.